2016
DOI: 10.12783/issn.1544-8053/13/4/3
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Contamination Hazards of Heavy Metals in Solid Residues from the Pyrolysis and Gasification of Wastewater Sewage Sludge

Abstract: most of the targeted heavy metals (hms) in sewage sludge ended up in solid residues after pyrolysis and gasification, such as Cu, Zn, Cr, Ni and Pb, which their residual rates were over 70%. The bioavailability of the hms in residues decreased despite their concentrations being higher compared with in sludge. The potential eco-toxicity of each HM were ceased after pyrolysis and gasification of sludge. It was particularly noted that HMs in steam gasification residue exhibited the lowest contamination levels. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…The BCR sequence includes the acid-soluble, reducible, oxidizable, and residual fractions of the metals, of which the acid-soluble fraction is regarded as the main mobile and bioavailable form [ 67 ], representing a greater risk for the surrounding environment. Reducible and oxidizable fractions are considered slow release fractions and can transform to acid-soluble species under acid conditions, whereas the residual fraction is relatively immobile with a low bioavailability; it is fixed in the soil lattice and hardly used by organisms [ 68 ]. The results of the fraction analysis are illustrated in Figure 8 .…”
Section: Resultsmentioning
confidence: 99%
“…The BCR sequence includes the acid-soluble, reducible, oxidizable, and residual fractions of the metals, of which the acid-soluble fraction is regarded as the main mobile and bioavailable form [ 67 ], representing a greater risk for the surrounding environment. Reducible and oxidizable fractions are considered slow release fractions and can transform to acid-soluble species under acid conditions, whereas the residual fraction is relatively immobile with a low bioavailability; it is fixed in the soil lattice and hardly used by organisms [ 68 ]. The results of the fraction analysis are illustrated in Figure 8 .…”
Section: Resultsmentioning
confidence: 99%
“…The scheme of linking WAS and biofuel production can be introduced as a promising approach. However, implementation of appropriate thermochemical processes and its optimum operating conditions are highly desirable based on the type and content of HMs in the WAS, as well as, reactor design and the presence of probable pre-/post-treatment techniques [206]. For example, pyrolysis process at lower temperatures around 400 to 600 °C has been found safer and efficient compared to gasification, liquefaction and incineration with higher temperatures/pressure, thereby increasing the emission of HMs into gaseous phase.…”
Section: Feedstockmentioning
confidence: 99%
“…Moreover, low temperature pyrolysis could contribute a considerable reduction on contamination level, bioavailability and environmental risk of HMs [67,206,207].…”
Section: Feedstockmentioning
confidence: 99%
“…The BCR sequence includes the acid-soluble, reducible, oxidizable, and residual fractions of metals, of which the acid-soluble fraction is regarded as the main mobile and bioavailable form [39], thereby representing a greater risk for agricultural productivity. Reducible and oxidizable fractions are considered slow-release fractions and can transform to acid-soluble species under acidic conditions, whereas the residual fraction is relatively immobile with low bioavailability [40]. The BCR analysis showed that the application of TSP+BC amendments (mass rate 1:3) at three different doses (3%, 5%, and 10%) induced the transformation of all three metals from soluble to stable forms.…”
Section: Bcr Fractions Of CD Pb and Cu In Tsp+bc-treated Soilmentioning
confidence: 99%